2012
DOI: 10.1002/app.36520
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy study of photodegradation of polymer modified asphalt binder

Abstract: The effect of solar radiation in the aging of the asphalt binder can be considered relevant in several countries due to the high level of insulation. This article deals with the comparative aging of a conventional asphalt binder and styrene‐butadiene‐styrene modified asphalt binder samples under the effect of weathering. The samples were exposed to cycles of xenon radiation, moisture, and temperature. The degradation of binders was analyzed by using the technique of Fourier transform infrared spectroscopy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Currently, chemiluminescence, thermogravimetry analysis, and oxygen consumption experiments have been implemented to study the polymer aging evolution. These investigations are based on the simulation of the aging process for polymers through a heating progress, and the signal changes are recorded as a function of time. However, these techniques can only provide statistic results for polymer aging at a macroscopic scale. In addition, Fourier transform infrared spectroscopy (FT-IR) has been regarded as the most conventional technique to detect the variations of functional groups during the polymer aging, such as hydroxyl, carbonyl, and ketone groups. However, the sensitivity of the FT-IR technique is not competent for ultratrace detection of these functional groups in early-stage aging. More importantly, all of the present techniques failed to give a three-dimensional evaluation on polymer aging. Therefore, it is highly desired to develop a sensitive and multidimensional evaluation strategy for the early-stage identification for polymer aging.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, chemiluminescence, thermogravimetry analysis, and oxygen consumption experiments have been implemented to study the polymer aging evolution. These investigations are based on the simulation of the aging process for polymers through a heating progress, and the signal changes are recorded as a function of time. However, these techniques can only provide statistic results for polymer aging at a macroscopic scale. In addition, Fourier transform infrared spectroscopy (FT-IR) has been regarded as the most conventional technique to detect the variations of functional groups during the polymer aging, such as hydroxyl, carbonyl, and ketone groups. However, the sensitivity of the FT-IR technique is not competent for ultratrace detection of these functional groups in early-stage aging. More importantly, all of the present techniques failed to give a three-dimensional evaluation on polymer aging. Therefore, it is highly desired to develop a sensitive and multidimensional evaluation strategy for the early-stage identification for polymer aging.…”
Section: Introductionmentioning
confidence: 99%
“…Under a long‐term service period, both asphalt and epoxy resin undergo various performance degradations under external environmental factors. These factors involve high temperature, sunlight (principally ultraviolet), oxygen, water, or a combination of these effects 6–11 . Herein, thermal‐oxidative aging affects the performance of EA binder, specifically increased modulus, reduced phase angle, and agglomeration of asphalt part 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…At present, several additives are used in asphalt modification such as crumb tyre rubber(CR) [2][3][4], styrene-butadiene-styrene block copolymer (SBS) [5][6][7][8][9][10][11][12][13][14][15], polyethylene (PE) [16][17][18][19][20][21][22][23][24], styrene-butadiene rubber (SBR) [25,26], polyethylene glycol terephthalate (PET) [27][28][29], biomass [30,31] asphalt [32]. The results found that the softening point increased accordingly with the increasing POE.…”
Section: Introductionmentioning
confidence: 99%